(untitled) (MAUSAM, 1983)
All monsoon depressions which formed during 1961- 74 over the Bay of Bengal and moved in westerly or westnorthwesterly directions have been composited to obtain the mean rainfall pattern around the primitive depression centre. Variations in the pattern and intensity of rainfall as the depression approach the Arabian Sea have been examined and discussed. Results indicate absence of large-scale rainfall activity near the depression centre. A primary zone of the heaviest fall occurs in the southwest sector about 200 to 400 km from the centre while a secondary zone of comparatively less rainfall amount is located about 800 km west of the depression centre. It is seen that when a depression is to the west of 80 deg. E, it gives considerably higher amount of rainfall sometimes twice of the amount released by the mean depression on an average than when it is to the east of 80 deg. E.